Pyrimethamine decreases levels of SOD1 in leukocytes and cerebrospinal fluid of ALS patients: A phase I pilot study. Issue 3 (April 2013) - Lange, Dale J.; Andersen, Peter M.; Remanan, Rahul; Marklund, Stefan; Benjamin, Daniel
Abstract The mutated SOD1 protein appears to have a gene dose-dependent effect on the severity and progression of ALS. Lowering of SOD1 protein levels might reduce severity and progression of the disease. The antimalarial drug pyrimethamine (PYR) was identified to cause a dose-dependent reduction in SOD1 protein levels in human cells in vitro. To determine if there was a similar effect in humans, we performed a phase I pilot study in 16 ALS patients with SOD1 mutations, 18 weeks in duration. Blood samples were obtained during all visits. The actin normalized leukocyte SOD1 levels were analyzed using Western blot. SOD1 content in the cerebrospinal fluid (CSF) was determined by ELISA and the SOD1 enzymic activity by spectrophotometric analysis using KO2. Clinical assessment of disease severity was assessed using Appel ALS scale and ALSFRS-R. The leukocyte SOD1 levels showed a significant reduction (p > 0.0001) by the third study visit and this reduction was sustained throughout the remainder of the study. CSF also showed a decrease in SOD1 protein content and enzymic activity in the two patients so tested. Thus, PYR use may be associated with a reduction in SOD1 in ALS patients. The significance is uncertain and further detailed study is required.